Dr. Seuss's children's books in ELT - Rulíková, Jana (Univerzita Pardubice, 2012)
The thesis concerns the issue of children's literature and its possible uses in English language teaching (ELT). For this purpose, picture books of an American author Dr. Seuss have been chosen. Firstly, the theoretical background is introduced. It deals specifically with the term children's literature, its definition, genre division, historical context and its importance to readers. It also focuses on the author, Dr. Seuss, his works and their potential for English language teaching and learning. Furthermore, it describes the learners involved and general objectives they are going to achieve. Secondly, the practical part presents five lessons that reflect the findings from the first part. It also contains a teacher's reflection and feedback from pupils.
Dětské knihy Dr. Seusse ve výuce anglického jazyka
Keywords: dětská literatura; Dr. Seuss; obrázkové knihy; výuka anglického jazyka; children's literature; picture books; English language teaching